Correlation of bone scintigraphy and histological findings in medial tibial syndrome. Issue 1 (1st February 2000) - Bhatt, R; Lauder, I; Finlay, D B; Allen, M J; Belton, I P
Abstract : Objective —To correlate bone scintigraphy and histopathological findings in patients with medial tibial syndrome. Methods —Twenty patients (32 limbs) with a clinical diagnosis of medial tibial syndrome had surgery. Bone scintigraphy before the operation was compared with the histological appearance of bone and periosteal specimens obtained at surgery. Results —Delayed bone scintigraphy showed normal appearance in 11 limbs, characteristic diffuse tubular pattern uptake in 16 limbs, and focal uptake in five. Periosteal histology disclosed fibrous thickening as the most common finding associated with increased vascularity, occasionally with chronic inflammatory cell infiltration, haemosiderin, and acid mucopolysaccharide deposition. Loss of osteocytes was the main finding of bone histology associated with some enlargement of lacunae and lamellar structure disruption. A grading system was used to score normal and abnormal histological appearance. For analysis the findings were regrouped to provide tables using Fisher's exact test. There was no correlation between bone scintigraphy and the histology of bone and periosteum, but two interesting observations were noted. Those cases with periosteal thickening had mostly normal bone scan appearance (p = 0.0028). Those cases with low levels of osteocyte loss had mostly abnormal bone scintigraphy. Conclusion —Abnormal histological appearance of bone and periosteum is a feature of medial tibial syndrome. These histological findings show poor correlation with bone scintigraphy. The exact pathogenesis of this syndrome remains unclear.